Abundance of Antarctic blue whales south of 60°S from three complete circumpolar sets of surveys - Branch, T. A. (J. Cetacean Res. Manage., 2023)
Sightings from the IDCR/SOWER austral summer surveys are analysed to provide abundance estimates for Antarctic (true) blue whales (Balaenoptera musculus intermedia) south of 60°S. The IDCR/SOWER ship-borne surveys have completely circled the Antarctic three times: 1978/79-1983/84 (CPI); 1985/86-1990/91 (CPII); and 1991/92-2003/04 (CPIII), covering strata totalling 64.3%, 79.5% and 99.7% of the ocean surface between the pack ice and 60°S. During the surveys, blue whale sightings were rare but were recorded in all regions. Raw sighting rates (schools per 1,000 n.mile of primary search effort) were 0.44 (CPI), 0.67 (CPII) and 1.48 (CPIII). Respective circumpolar abundance estimates were 453 (CV=0.40), 559 (CV=0.47) and 2,280 (CV=0.36), with corresponding mid-years of 1981, 1988 and 1998. The CPIII estimates are the most complete and recent for this subspecies. When adjusted for unsurveyed regions in a simple way, the estimated circumpolar rate of increase is 8.2% (95% CI=1.6–14.8%) per year; nevertheless, Antarctic blue whales still number far less than the estimated 202,000-311,000 that existed before exploitation. These abundance estimates are negatively biased because some Antarctic blue whales may have been north of 60°S or in the pack ice at the time of the surveys and because a small number of blue whales on the trackline were probably missed. Furthermore, a small proportion of pygmy blue whales, probably less than 1%, may have been included in the sightings.